Local culture-based English language teaching for young learners: A systematic literature review - Eko Heriyanto; Sri Wuli Fitriati; Zulfa Sakhiyya (Scientific English, 2026)
This study examines the integration of local culture into English language teaching (ELT) for young learners through a systematic literature review (SLR). Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, peer-reviewed studies published between 2013 and 2023 were identified from Scopus, ERIC, and Google Scholar databases. The initial search yielded 37 articles, of which 10 met the inclusion criteria and were selected for in-depth analysis. The selected studies were analyzed thematically using Braun and Clarke’s framework to identify recurring patterns in the implementation of local culture integration in ELT. The thematic synthesis revealed five major themes: pedagogical benefits, culturally responsive teaching practices, cultural identity and intercultural awareness, teacher readiness and professional challenges, and curriculum and policy implications. Across the reviewed studies, integrating local culture into ELT was found to support students’ motivation, engagement, communicative competence, and classroom participation by connecting language learning to familiar socio-cultural contexts. The findings further showed that contextual teaching practices, including the use of local stories, games, and culturally relevant materials, contributed to more meaningful learning experiences while fostering cultural identity and intercultural awareness. However, several challenges emerged, including limited teacher preparedness, difficulties in designing culturally responsive learning activities, insufficient contextual teaching resources, and the continued dominance of foreign cultural content in ELT materials. Overall, the review highlights the importance of teacher professional development, contextualized learning resources, and curriculum support in promoting culturally responsive ELT practices for young learners.